Simulation of Material Transport in a Sag Mill with Different Geometric Lifter and Pulp Lifter Attributes Using Dem - Gutierrez-Silva, A; Gonzalez-Cornejo, F (Springer, 2019)
A Discrete Elements Method (DEM) study of load movement within a SAG mill 12,192 × 7620 (40′ × 25′) in normal operating conditions is performed. The purpose is to determine how the geometry of the lifters affects the kinetics of the load inside the mill. Specifically, the changes produced by the incorporation of inclined lifters and spiral or helicoidal pulp lifters to the kinetics are evaluated. Four study cases are identified: first, the base case corresponds to a conventional geometry; the second case corresponds to inclined lifters incorporation; third case corresponds to a mill with helicoidal discharge; and the fourth case corresponds to a mill with inclined lifters and helicoidal pulp lifters. To save computational resources, the water that enters the mill has been modeled by varying the coefficient of restitution. The results of a series of experiments are presented to determine how this coefficient varies when having impacts on surfaces with different liquid levels. A comparative analysis is made of the following variables: mean transport speed and material flow, for normal operating conditions. Taking as reference the mill with straight lifters and radial pulp lifters (case 1), the case with the inclined lifters and radial pulp lifters increases the material discharge flow less to 76 mm of size by 5.1%, and this value increases even more when the helicoidal pulp lifters are incorporated reaching a 58.6%. The most significant change is seen in the flow through the grates and the pulp lifters discharge, which can increase substantially improving the operation. © 2018, The Society for Mining, Metallurgy & Exploration.